Proceedings of the 2nd Conference on Conversational User Interfaces 2020
DOI: 10.1145/3405755.3406126
|View full text |Cite
|
Sign up to set email alerts
|

User Preference and Categories for Error Responses in Conversational User Interfaces

Abstract: Error messages are frequent in interactions with Conversational User Interfaces (CUI). Smart speakers respond to about every third user request with an error message. Errors can heavily affect user experience (UX) in interaction with CUI. However, there is limited research on how error responses should be formulated. In this paper, we present a system to study how people classify different categories (acknowledgement of user sentiment, acknowledgement of error and apology) of error messages, and evaluate peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…CBL can be used for a range of research projects, including -designing dialogues of conversational user interfaces, for example by testing one dialogue design versus another in A/B testing, -comparing effects of input modalities, e.g. by running an experiment with a text-based chatbot and comparing user perceptions or behavior to running the same experiment with a speaking chatbot, -investigating effects of errors on user experience (Yuan, Brüggemeier, Hillmann, & Michael, 2020), -examining effects of privacy violations (Sannon, Stoll, DiFranzo, Jung, & Bazarova, 2020) or conversational privacy (Brüggemeier, & Lalone, 2022a), -studying effects of different voices on user behaviour (like male, female and neutral voices (Lee, Nass, & Brave, 2000); or voices with different accents, e.g. British vs. American accents (Tamagawa, Watson, & Kuo, 2011)), -and investigating effects of different languages and cultures (Cambre, & Kulkarni, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…CBL can be used for a range of research projects, including -designing dialogues of conversational user interfaces, for example by testing one dialogue design versus another in A/B testing, -comparing effects of input modalities, e.g. by running an experiment with a text-based chatbot and comparing user perceptions or behavior to running the same experiment with a speaking chatbot, -investigating effects of errors on user experience (Yuan, Brüggemeier, Hillmann, & Michael, 2020), -examining effects of privacy violations (Sannon, Stoll, DiFranzo, Jung, & Bazarova, 2020) or conversational privacy (Brüggemeier, & Lalone, 2022a), -studying effects of different voices on user behaviour (like male, female and neutral voices (Lee, Nass, & Brave, 2000); or voices with different accents, e.g. British vs. American accents (Tamagawa, Watson, & Kuo, 2011)), -and investigating effects of different languages and cultures (Cambre, & Kulkarni, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Given the intriguing and multifaceted research implications but also the strategic business relevance of this subject, studies on how to identify users' interests thrived. Research works focused on several different domains, including, e.g., spreadsheets (Bishop & McDaid, 2008), navigation systems (Wen et al, 2013), and social networks (Antelmi, 2019), but also considered locations of users (Preo t ¸ iuc-Pietro and Cohn, 2013) and preferred user interfaces (Yuan et al, 2020). At the same time, the approaches used for analysing users' behaviours also evolved.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study surveying people’s perceptions of error message types spoken by CAs found that the participants preferred error messages that included an apology, an explanation of what went wrong, a suggestion on how to fix the problem, or a neutral acknowledgment of the error [ 30 ]. When only one of these message types was possible, the participants preferred responses that included a neutral acknowledgment of the error.…”
Section: Introductionmentioning
confidence: 99%